Ear symptoms accompanying temporomandibular joint diseases - Kaygusuz, Irfan; Karlida?, Turgut; Keleş, Erol; Yalçin, Sinasi; Yildiz, Mücahit; Alpay, Hayrettin Cengiz (My University, 2006)
OBJECTIVES: We investigated symptoms of otologic diseases in patients with temporomandibular joint diseases. PATIENTS AND METHODS: The study included 44 patients (26 females, 18 males; mean age 36+/-10.7 years; range 21 to 58 years) with temporomandibular joint disease. A questionnaire was administered to the patients to inquire into otological symptoms accompanying temporomandibular joint disease. RESULTS: Temporomandibular joint disease was bilateral in 11 patients. Accompanying otological symptoms were as follows: click voice with jaw movements (n=21; 47.7%), headache (n=15; 34.1%), pain in the ear with jaw movements (n=14; 31.8%), tinnitus (n=8; 18.2%), fullness in the ear (n=6; 13.6%), vertigo or dizziness (n=6; 13.6%), and hearing loss (n=3; 6.8%). Pure-tone audiometry revealed sensorineural hearing loss in one patient, being 28 dB on the right and 30 dB on the left. CONCLUSION: Our findings suggest that otologic symptoms may accompany temporomandibular joint diseases, requiring that patients presenting with otologic symptoms must be investigated for temporomandibular joint diseases.
Temporomandibüler eklem hastaliklarinda kulakla ilgili semptomlar.
Keywords: Adult; Dizziness; Female; Hearing Loss; Humans; Male; Middle Aged; Temporomandibular Joint Disorders; adult; article; dizziness; female; hearing loss; human; male; middle aged; pathophysiology; temporomandibular joint disorder